Association of the Depth of Invasion wth Lymph Node Metastasis in Oral Squamous Cell Carcinoma Patients - A Retrospective Study - Aklesha Behera1 , Hannah.R2 , Abilasha Ramasubramanian3 , Pratibha Ramani4 , (Institute of Medico-legal Publications Pvt Ltd, 2020)
Oral squamous cell carcinoma is the most common oral malignancy representing upto 80 % to 90% ofall malignancies of oral cavity. In Indian population, it ranks 3rd of all carcinomas. Dietary factors andexternal factors like tobacco, smoking and alcohol consumption are the major causes for progression of oralsquamous cell carcinoma. Histopathologically, the tumor progression is assessed by TNM staging. It is themost common and widely practised histomorphological evaluation of tumor progression. Depth of invasionis also another tool for evaluating tumor progression in OSCC and is also used widely in every clinicohistopathological slide evaluation and diagnosis. In this study, a correlation was made between depth ofinvasion and nodal metastasis. All the data was collected after checking 86,000 patient records. Details suchas age, sex, pathological TNM staging, depth of invasion and cases with nodal metastasis were tabulated.Association was made using the IBM SPSS version 20.0. Pearson chi square test did not show any significantassociation between depth of invasion with nodal metastasis. Other factors like pattern of invasion, tumordifferentiation, site of the lesion as well as the age of the patient has to be taken into consideration for futureassessment.